Tinjauan Filosofis Laku Keberagaman di Era Media Sosial - Al Walid, Khalid (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
The behavior of Indonesian people is increasingly easy to communicate with social media, such as discussing and preaching between individuals or groups with others. Phenomenon that occurs in strength and diversity with productive religious discourse, but religious continuity, counterproductive and discussion of the shallowness of ideas. The consequence is the incitement of hatred and slander. Through this research, the author found that the root problem of the fundamental behavior of our increasingly destructive diversity in the midst of the media is the very low socialization of reflective-philosophical reading, studying and responding to various phenomena that arise through social media. The critical analysis method is Mulla Sadra based on philosophical access to trans-substantial motion. This study concluded that the low level of awareness, low awareness, who gave birth again, did not want to think hard, instant, flexible and simplistic in religion. Implications of research that provide a new perspective that criticism is very important to be cultivated in people's lives.